Pengaruh Faktor Produksi Petani Karet Rakyat Dengan Bahan Tanam Klon Unggul - Gustina Siregar (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
This Study uses multiple linear regression analysis of factors that influence farmers' production of rubber clones with superior planting materials, meticulous production factors in the area of land, seed, fertilizer and medicine. The result obtained that simultaneously (simultaneous) production of rubber farmers affected by land area, fertilizer and medicine by 96,6% and the rest is influenced by factors other than variable by 3,4% to the calculated value of F-> F-table (@=0,05). Partial Production of the most influential factor in the fertilizer value of t-count > t-table, while the factors of production that do not significantly affect the area and the drugs with the calculated value of t<t-table (@=0,05)